Explaining Macro-Social Change with Archived Data: Reading against the Grain - Jane Gray (Przeglad Socjologii Jakosciowej, 2019)
This article examines some of the opportunities and challenges associated with using archived qualitative data to explain macro-social change through a biographical lens. Using examples from a recent research project on family change in Ireland, I show how working across qualitative datasets provided opportunities for generating new explanations of social change by ‘reading against the grain’ of established social science narratives and tracing innovation in social practices. I also discuss some of the methodological challenges associated with working across datasets and how we addressed them in the study.